the Effect of Potassium Fertilizer and Paclobutrazol Application Time on the Growth and Yield of Sweet Corn in Peat Soil - Maulidi, Maulidi; Darussalam, Darussalam; Annisa, Baaqiy Amri (AGRITROPICA : Journal of Agricultural Sciences, 2025)
For optimal effects on sweet corn growth and yield, it is critical to determine when to apply Paclobutrazol and how much potassium fertilizer to apply. The goal of the study is to determine the optimal K fertilizer dosage and Paclobutrazol application timing for sweet corn plant growth and yield in peat soil in West Kalimantan, Indonesia. A split-plot design with two factors was used for the study. The time of application of Paclobutrazol 1500 ppm (W) as the main plot and dosage of potassium fertilizer (K) as the subplot. Paclobutrazol's application period only suppressed plant height and leaf number, whereas potassium application markedly enhanced sweet corn yield. Paclobutrazol's application period only reduced plant height by 13.06-28.42 cm. The 5-week (WAP) Paclobutrazol spraying period had the most significant impact on reducing sweet corn plant height. Potassium fertilization significantly improved sweet corn yield components. Doses of 200–300 kg·ha⁻¹ increased cob weight, husk-free cob weight, and cob length relative to lower doses, while cob diameter responded effectively from 100 kg·ha⁻¹ onward. The highest overall performance was achieved at 300 kg·ha⁻¹, indicating that this dose was the most effective for maximizing sweet corn yield under the study conditions.